"Good Design is Good Business": An Empirical Conceptualization of Design Management Using the Balanced Score Card. Issue 1 (22nd November 2021) - Parkman, Ian; Malkewitz, Keven
Abstract : Despite the increasing attention Design Management has received from academics and practitioners a definitive conceptualization or a widely‐agreed upon empirical measure of the construct does not yet exist. This paper proposes a new measurement of Design Management based on the informational elements captured in product design briefs. Exploratory Factor Analysis results suggest that Design Management is made up of eleven clusters: F1 Customer Insights; F2 Business Model; F3 Aesthetics; F4 Authenticity; F5 Symbolic/Experiential Value; F6 Functional Value; F7 Promotions/Distribution; F8 Sustainability; F9 Production/Development; F10 Project Management; F11 Risk/Safety. Our analysis describes how these factors show differing effects on measures of firm performance at the product project‐ and competitive advantage‐levels (for example, F1, F3, and F9 are strongly and significantly positively related to both sets of measures while F4, F5, and F8 are more important to the competitive advantage of a firm than to any individual product offering). Our findings are organized and discussed using the Balanced Score Card for Design Management tool made up of (1) Customer Perspective (Design as differentiator); (2) Process perspective (Design as coordinator); (3) Learning and Innovation perspective (Design as transformer); and (4) Financial perspective (Design as good business).